Effects of chitin degradation products N-acetylglucosamine and N, Nʹ-diacetylchitobiose on chitinase activity and bacterial community structure in an incubated upland soil. Issue 3 (3rd May 2020) - Shimoi, Yusuke; Honma, Daichi; Kurematsu, Airi; Iwasaki, Yukari; Kotsuchibashi, Yohei; Wakikawa, Yusuke; Saito, Akihiro
ABSTRACT: Chitin, which is the polymer of N -acetylglucosamine (GlcNAc) linked by β1, 4 glycoside bonds, has been reported as a soil amendment to mitigate plant soil diseases, increasing the population of chitin-degrading bacteria, and chitinolytic enzymatic activity in the soil. In some chitin-degrading bacteria, whose chitinolytic systems have been intensively studied, the chitin degradation product N, Nʹ -diacetylchitobiose {(GlcNAc)2 } induces expression of genes for chitinases whereas GlcNAc does not. To evaluate the effects of these mono- and disaccharides on the population and activity of chitinolytic bacteria in soil, we investigated the chitinolytic enzyme activity and bacterial community structure in an incubated upland soil supplemented with GlcNAc or (GlcNAc)2 . The added GlcNAc and (GlcNAc)2 (2 mg g −1 ) were consumed within 1 d when incubated at 25°C. Chitinase activity was induced by (GlcNAc)2 and chitin after 1-d and 7-d incubation, respectively, but not by GlcNAc. N -acetylglucosaminidase (GlcNAcase) activity was induced by GlcNAc but was lower than those by (GlcNAc)2 and chitin. Amplicon sequencing analysis targeting 16S rRNA genes demonstrated that both GlcNAc and (GlcNAc)2 significantly increased the rate of the order Bacillales, but the compositions of Bacillales differed from each other: the family Planococcaceae significantly increased in either GlcNAc- or (GlcNAc)2 -added soil, but the genera Bacillus and Paenibacillus were increased mainly by GlcNAc and (GlcNAc)2, respectively. The family Streptomycetaceae of the order Actinomycetales was significantly increased by (GlcNAc)2 and chitin, but GlcNAc did not. Thus, GlcNAc and (GlcNAc)2, which were promptly consumed in the incubated soil, indicated partly similar but distinctive effects on chitinolytic enzyme activity and bacterial communities. Both aminosugars increased GlcNAcase activity and the population size of Planococcaceae. GlcNAc increased Bacillus . Chitinase activity and the populations of Paenibacillus and Streptomycetaceae, a number of strains of which are known as potent chitin-degraders, were increased by (GlcNAc)2, but not by GlcNAc.